Motion Simulation of the Pulsing Mechanism of Continuously Variable Transmission based on Visual Basic - Huang Yi; Xu Jianqiang; Xu Haiyang; Lin Jianbin; Wu Yongkun; Liu Kaichang (Jixie chuandong)
With the visual program design features of Visual Basic of being object- based and event-driven that contains integrated development environment,a motional simulation of the continuously variable transmission（ CVT） pulsing mechanism is carried out,the mechanical performance of the impulse CVT is studied from the motion simulation. A quadrilateral efficient pulsing mechanism is discussed.